2021
DOI: 10.1029/2020gl088369
|View full text |Cite
|
Sign up to set email alerts
|

Resource Colimitation Drives Competition Between Phytoplankton and Bacteria in the Southern Ocean

Abstract: Phytoplankton growth in large areas of the Southern Ocean is regulated by the micronutrient iron (Fe)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 78 publications
3
18
0
Order By: Relevance
“…These findings are in agreement with the results of Ratnarajah et al. (2021), who used a mechanistic model of FL bacteria‐phytoplankton competition in an idealized setting: Luxury Fe uptake by FL bacteria exacerbates the competition between FL bacteria and phytoplankton. Furthermore, in highly seasonal regimes, such as at mid‐ and high‐latitudes, competition for Fe increases over the course of the productive season as the accumulation of LDOC produced by phytoplankton exudation, sloppy feeding, and zooplankton excretion stimulates the FL bacterial activity (Sturluson et al., 2008).…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…These findings are in agreement with the results of Ratnarajah et al. (2021), who used a mechanistic model of FL bacteria‐phytoplankton competition in an idealized setting: Luxury Fe uptake by FL bacteria exacerbates the competition between FL bacteria and phytoplankton. Furthermore, in highly seasonal regimes, such as at mid‐ and high‐latitudes, competition for Fe increases over the course of the productive season as the accumulation of LDOC produced by phytoplankton exudation, sloppy feeding, and zooplankton excretion stimulates the FL bacterial activity (Sturluson et al., 2008).…”
Section: Resultssupporting
confidence: 92%
“…Our results are thus consistent with previous measurements in the subarctic Pacific, which reported that FL bacteria account for ∼20%–40% of the total biological Fe uptake (Tortell et al., 1996). In addition, various field and incubation and modeling studies in the Southern Ocean (Boyd et al., 2012; Fourquez et al., 2020; Kuparinen et al., 2011; Ratnarajah et al., 2021) showed that FL bacteria are a significant competitor with phytoplankton for Fe if LDOC is available.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, phycosphere bacteria can stimulate the growth of specific phytoplankton by producing growth hormones [5] or supplying a limiting nutrient, such as a B-vitamin [6][7][8] or fixed-nitrogen [9]. Conversely, phycosphere bacteria can manipulate phytoplankton communities by secreting algicidal molecules (e.g., roseobacticides) that selectively kill certain phytoplankton [10] or by competing for essential nutrients [11,12]. Even small shifts in phytoplankton communities can alter how much organic carbon is recycled in the surface ocean or exported to deep water [13] since phytoplankton taxa vary in their C:N:P ratio [14], morphology, and sinking rates [15].…”
Section: Introductionmentioning
confidence: 99%